Mathematics Learning Assistance Home Visit In the Village Made to Develop Middle School Students' Learning Response - Nurul Aini, Khafidhoh; Irwan Hermawan, Arief; Nadhifah, Muslimatun (Shof Journal of Social Impact, 2024)
The low interest in student learning in certain subject also affects the value os students’ learning attitudes in following the online teaching and learning process. The specific objective of this study is to emphasize learning assistance to improve student learning outcomes in the face of online or distance-based schools. The method used is the method of observation by describing the state of object, empasizing theree aspects of attitude values: cognitive (knowledge), affective (feelings and emotions),adn conative (desire). The result of the research is discovery learning method shows high effectiveness in mathematic. The percentage of attitude value of the 3 research object showed interst in the concept and material off 66,67%, satisfaction of mentoring activities was 100%, cofidence in doing exercise was 33,33%, and understanding wass 100% counted the number of questions answered successfully.